2019
DOI: 10.1177/2047487319859974
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based cardiac rehabilitation for patients with catheter ablation for persistent atrial fibrillation: A randomized controlled clinical trial

Abstract: Aims The efficacy and safety of cardiac rehabilitation for patients with persistent atrial fibrillation who restored sinus rhythm after catheter ablation remains unclear. The aim of the present study was to evaluate the effects of cardiac rehabilitation on exercise capacity, inflammatory status, cardiac function, and safety in patients with persistent atrial fibrillation who had catheter ablation. Methods In this randomized controlled study, 61 patients treated with catheter ablation for persistent atrial fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 32 publications
0
87
0
Order By: Relevance
“…The 12 RCTs included 819 patients (408 allocated to experimental groups and 411 allocated to control groups). Four RCT exercise interventions were aerobic (Osbak et al, 2012 ; Malmo et al, 2016 ; Joensen et al, 2019 ; Nourmohammadi et al, 2019 ), one was anaerobic (Zeren et al, 2016 ), three were aerobic combined with anaerobic (Hegbom et al, 2007 ; Risom et al, 2016 ; Kato et al, 2019 ), one was Qigong (Pippa et al, 2007 ), and three were Yoga (Lakkireddy et al, 2013 ; Wahlstrom et al, 2017 ; Wahlström et al, 2020 ). The details of all included studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 12 RCTs included 819 patients (408 allocated to experimental groups and 411 allocated to control groups). Four RCT exercise interventions were aerobic (Osbak et al, 2012 ; Malmo et al, 2016 ; Joensen et al, 2019 ; Nourmohammadi et al, 2019 ), one was anaerobic (Zeren et al, 2016 ), three were aerobic combined with anaerobic (Hegbom et al, 2007 ; Risom et al, 2016 ; Kato et al, 2019 ), one was Qigong (Pippa et al, 2007 ), and three were Yoga (Lakkireddy et al, 2013 ; Wahlstrom et al, 2017 ; Wahlström et al, 2020 ). The details of all included studies are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The effect of physical exercise on exercise ability was measured by the 6MWT. Five RCTs (Pippa et al, 2007 ; Osbak et al, 2012 ; Zeren et al, 2016 ; Joensen et al, 2019 ; Kato et al, 2019 ) reported the results of 6MWTs, which were improved after physical exercise in AF patients (SMD = 0.69, 95%CI: 0.19–1.19; p = 0.007) ( Figure 6 ) with high heterogeneity ( I 2 = 70.6%, p = 0.009). After meta-regression analysis, the training duration was selected as the heterogeneity factor ( p = 0.047) from the possible factors (training period, training mode, training duration and exercise intensity) that may cause heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current issue of European Journal of Preventive Cardiology publishes an interesting study from Kato and colleagues including 61 patients who underwent catheter ablation for persistent atrial fibrillation. 6 The authors randomized patients to catheter ablation alone versus catheter ablation plus a cardiac rehabilitation programme that included endurance and resistance training at least three times per week. After six months, patients who underwent exercise training significantly improved exercise capacity compared with the control group and significantly improved their systemic inflammatory status.…”
mentioning
confidence: 99%